2015
DOI: 10.1187/cbe.14-10-0184
|View full text |Cite
|
Sign up to set email alerts
|

Building National Capacity for Research Mentor Training: An Evidence-Based Approach to Training the Trainers

Abstract: This article describes the development, implementation, evaluation, and impact of a train-the-trainer workshop designed to promote widespread dissemination of an evidence-based research mentor training curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 41 publications
(65 reference statements)
1
58
0
Order By: Relevance
“…Historically, it has not been the standard for mentors to receive formal mentoring skills training. Instead, mentors typically “learned” by example, trial and error, or peer observation, However, several recent studies have described promising approaches to mentoring training. Pfund et al .…”
Section: Discussionmentioning
confidence: 99%
“…Historically, it has not been the standard for mentors to receive formal mentoring skills training. Instead, mentors typically “learned” by example, trial and error, or peer observation, However, several recent studies have described promising approaches to mentoring training. Pfund et al .…”
Section: Discussionmentioning
confidence: 99%
“…Such metrics include number of mentees, frequency and quality of mentor-mentee contact, routine use of specific mentoring tools such as the Individual Development Plan (IDP), mentee productivity (e.g., published papers, funded grants), and mentor-mentee satisfaction with the mentoring relationship. Eventually, it will be important to document whether intensive mentor training such as the program described in this paper or others 11 results in an increase in the likelihood that mentees will remain in academic research careers. Improvements in self-efficacy around research skills have been reported in early stage learners with designated training programs, 59,60 but the impact of mentorship training on mentee self-efficacy has not been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…6,1113 A recently-published randomized controlled trial by Pfund et al conducted at 16 academic health centers randomized mentors in the intervention arm to an 8-hour case-based curriculum focused on mentoring competencies, and compared mentor and mentee reports of mentors’ competency skills post-training to those from an untrained control group. 6 Importantly, besides improvements in the mentors’ perceptions of mentoring competency after receiving the training intervention, mentees of trained mentors also reported improvements in the mentoring skills of their mentors, even though the mentees were blinded to mentor assignment.…”
Section: Introductionmentioning
confidence: 99%
“…The "Entering Mentoring" curriculum, an evidence-based mentor training has been foundational in attempting to address disparities and developing culturally competent mentors in the biomedical sciences (13,15,16). In recent years, the large-scale interventions developed by the National Research Mentoring Network consortium have begun to change the national narrative around mentor responsibilities and the importance of developing the cultural competence of mentors (17).…”
Section: The Central Role Of Research Faculty In Shaping Research Expmentioning
confidence: 99%